Macrophages Inhibit Ciliary Protein Levels by Secreting BMP-2 Leading to Airway Epithelial Remodeling Under Cigarette Smoke Exposure - Wang, Zhigang; Liang, Wenzhang; Ma, Cuiqing; Wang, Jiachao; Gao, Xue; Wei, Lin (Frontiers in Molecular Biosciences, 2021)
Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease with high morbidity and mortality worldwide. So far, smoking is still its leading cause. The characteristics of COPD are emphysema and airway remodeling, as well as chronic inflammation, which were predominated by macrophages. Some studies have reported that macrophages were involved in emphysema and chronic inflammation, but whether there is a link between airway remodeling and macrophages remains unclear. In this study, we found that both acute and chronic cigarette smoke exposure led to an increase of macrophages in the lung and a decrease of ciliated cells in the airway epithelium of a mouse model. The results of in vitro experiments showed that the ciliary protein (β-tubulin-IV) levels of BEAS-2B cells could be inhibited when co-cultured with human macrophage line THP-1, and the inhibitory effect was augmented with the stimulation of cigarette smoke extract (CSE). Based on the results of transcriptome sequencing, we focused on the protein, bone morphogenetic protein-2 (BMP-2), secreted by the macrophage, which might mediate this inhibitory effect. Further studies confirmed that BMP-2 protein inhibited β-tubulin-IV protein levels of BEAS-2B cells under the stimulation of CSE. Coincidentally, this inhibitory effect could be nearly blocked by the BMP receptor inhibitor, LDN, or could be interfered with BMP-2 siRNA. This study suggests that activation and infiltration of macrophages in the lung induced by smoke exposure lead to a high expression of BMP-2, which in turn inhibits the ciliary protein levels of the bronchial epithelial cells, contributing to the remodeling of airway epithelium, and aggravates the development of COPD.